Strategi Pemasaran Melalui Media Sosial Dalam Menaikkan Penjualan Idealistina Shop - Risnaningsih, Inne; Nenawati, Lavina; Haris Fadhillah, Muhammad (Universitas Koperasi Indonesia, 2023)
In various district now is being advanced so it affects human activities, they often used internet and shopisticated goods to their daily activites. These makes people used internet for online shopping so the online business has a higher potential. But there are so many competitors so Idealistina Shop need a research to develop online business using the social media people used in daily activities. This research used descriptive qualitative method. The results of this research is Idealistina Shop implemented marketing mix strategy (Product, price, promotion, place) and Idealistina Shop needs Growth Oriented Strategy as the results of IFAS and EFAS strategy implementation because the results shows Idealistina Shop has a good opportunities and strengths to develop the business.Idealistina Shop recommended to recruit a marketing employee because this shop doesn’t have any employee to develop the marketing strategy, other than that Idealistina Shop needs to improve the quality of customer services, endorse influencers use advertisement features on social media.